Effects Of Lactobacillus Plantarum Dr7 On Stress And Anxiety In Adults: A Randomised, Double-Blind, Placebo-Controlled Study - Chong, Hui Xian (2020)
Mental health represents a complex and complicated public health problem which has wide-ranging social and economic implications, as well as stark consequences for physical health. Probiotics have been reported to exert beneficial effects along the gut-brain axis. Lately, much interest was generated in the potential role of gut flora in mental disorders. This randomized, double-blind and placebo-controlled human study aimed to evaluate such properties of Lactobacillus plantarum DR7 and its possible underlying mechanisms of action in stressed adults for a period of 12 weeks.